PENCEGAHAN ANEMIA PADA REMAJA DAN PENATALAKSANAAN SECARA NON FARMAKOLOGI DI SMK N 1 REMBANG - Alvi Ratna Yuliana; Dian Arsanti Palupi; Dessy Erliani Mugita Sari; Endra Pujiastuti; Dwi Susiloningrum; Ricka Islamiyati (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2024)
Adolescent girls are a vulnerable group to experience anemia, if there are no prevention efforts, awareness among adolescents about the problem of anemia will affect problems in growth and development, both physically and academically. The main cause of anemia is insufficient intake of iron which cannot be obtained without only by taking blood-boosting drugs but this can be done by consuming a variety of foods that fulfill the nutrients containing iron, vitamins to prevent anemia, where teenagers nowadays pay less attention to healthy food intake. The purpose of this community service is to increase the level of student knowledge/ students through education about anemia, knowing the risk factors for anemia in adolescents, knowing the physical characteristics or symptoms and the consequences that arise from anemia and providing education about the treatment of anemia in addition to using pharmacological drugs, one of which is by consuming foods that contain Contains vitamins and iron to increase Hemoglobin levels in the blood. The activity method consists of three, namely planning, implementation and evaluation. This counseling was carried out offline at SMKN 1 Rembang with 40 students. Based on the results of the pre-test and post-test, it can be concluded that there was an increase in students' knowledge about anemia prevention and non-pharmacological management. increasing knowledge of young women before and after education